Unveiling The Impact of Collaboration-Oriented Culture on the Sustainability Report Quality: The Role of Stakeholder Pressure - Diah Agustina Prihastiwi; Atika Atika; Ari Nurul Fatimah; Evy Rahman Utami (JASF: Journal of Accounting and Strategic Finance, 2025)
Purpose: This research attempts to reveal how a team-centric culture impacts the quality of sustainability reports and how stakeholder pressure influences those linkages. Method: This study employs a quantitative methodology. The research sample comprised 64 energy industry companies from 2020 to 2024. Based on the purposive sampling employed, this research consists of 56 energy companies (260 observations). Secondary data from annual reports and corporate sustainability reports were utilised. The data were processed using STATA software. Findings: The findings show that energy companies that prioritise human capital development do not impact on the quality of sustainability reports, according to the fixed effect estimate model. Furthermore, pressure from institutional shareholders does not persuade companies to generate better sustainability reports. This finding aligns with other types of stakeholder pressure, both from creditors and employees. Other findings suggest that only company age can be an indicator of companies producing better-quality sustainability reports. Furthermore, several estimation models found that company size and profitability (return on assets) play a role in encouraging better-quality sustainability reports. Implications: The research findings indicate that all energy companies in Indonesia have not yet used assurance services to verify the information included in their sustainability reports. The findings provide practical implications for regulatory bodies, including the Indonesian Financial Accounting Standards Board-Institute of Indonesia Chartered Accountants (IAI) and the Financial Services Authority (OJK), regarding sustainability report verification regulations to minimise negative narcissism practices. Novelty/Value: This study focuses on the quality of the sustainability report related to the company's culture. Based on the theoretical perspective, this study uses institutional theory and stakeholder theory. Additionally, this study took into account the moderating effect of stakeholder pressure, which might have an impact on managerial choices.